(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Covid-19 pandemic outbreak forced many schools and colleges to remain closed temporarily. Various schools, colleges, and universities have discontinued in-person teaching and implemented virtual classes. Graduate students experience taking virtual internship programs and encounter challenges such as internet connection, device availability, working students and working environment, and limited opportunities in hospitality management and entrepreneurship. According to the data, the bulk of the respondents are between the ages of 21 and 25. Most of them are male and 24 years old in terms of the respondent’s employment status amidst the pandemic. Of the respondents, 100 percent, 26 respondents are employed. The majority of the respondents strongly agree with the challenges they encountered in terms of internet connection, device availability, working students and working environment, and limited opportunities in hospitality management and entrepreneurship during their virtual internship program. Based on the gathered data and conclusions drawn, researchers formulated solutions that can be recommended on the challenges encountered and opportunities of BSHM graduates of BCP in internship programs amidst the pandemic.